Assessment of self-reported perception and aspirations of online undergraduate students regarding STEM fields - Jordan Norwood; Felix M. Pabon-Rodriguez; Angel L. Figueroa-Rosado (Discover Education)
Abstract Understanding the experiences, perceptions, and barriers of students is critical to address disparities and fostering equity, particularly in the rapidly growing domain of online education. This study explored these factors among undergraduate students from an online math program at a Midwestern University, focusing on factors influencing the likelihood of pursuing STEM careers. An online survey was distributed to eligible participants, and quantitative and qualitative responses are analyzed. Descriptive statistics and a Bayesian logistic regression model were used to analyze the data. The results showed that 95.8% of respondents viewed the university as providing a supportive environment, and 54.2% felt that adequate resources were available for STEM success. Despite this, many participants highlighted unique challenges faced by underrepresented groups. The Bayesian analysis revealed key predictors of STEM pursuits, including positive associations with financial stability (83% probability of positive effect), participation in STEM workshops (83%), and confidence in STEM success (77%). Negative associations were observed for difficulty in career decision-making (87% probability of negative effect) and age (94% probability of negative effect). While many participants expressed confidence in STEM and acknowledged the supportive environment provided by the university, these findings underscore the importance of targeted interventions to address barriers and foster equitable participation in STEM, particularly in online education settings.